The religious thought of conservative Judaism: an analysis - Abdul Rahim, Adibah (2015)
Conservative Judaism claimed to be in the middle position between Orthodox and Reform Judaism attempting to maintain basic traditions while adapting to modern life. In its approach to reconstruction of religious thought, this position argued that to meet the challenges of the modern world, the key concepts of faith have to be redefined and reinterpreted in the light of modern science and knowledge. This paper highlights selected issues advocated by Conservative Judaism for reconstruction of religious thought, and provides an objective analysis on its position. It was found that despite of claiming themselves as belong to mediating position, Conservative Judaism seemed to ignore their scriptures and depended much on human interpretations. This is obviously contradicted to an Islamic approach which upholds that the fundamental sources of the Qur’an and Sunnah should always be referred to as primary references despite our reliance on modern knowledge and rational inquiries.